Quantifying the Dietary Overlap of Two Co‐Occurring Mammal Species Using DNA Metabarcoding to Assess Potential Competition - Aurelie M. Kanishka; Christopher MacGregor; Linda E. Neaves; Maldwyn John Evans; Natasha M. Robinson; Nick Dexter; Chris R. Dickman; David B. Lindenmayer (Ecology and Evolution)
ABSTRACT Interspecific competition is often assumed in ecosystems where co‐occurring species have similar resource requirements. The potential for competition can be investigated by measuring the dietary overlap of putative competitor species. The degree of potential competition between generalist species has often received less research attention than competition between specialist species. We examined dietary overlap between two naturally co‐occurring dietary generalist species: the common brushtail possum Trichosurus vulpecula and the bush rat Rattus fuscipes. To gauge the potential for competition, we conducted a diet analysis using DNA extracted from faecal samples to identify the range of food items consumed by both species within a shared ecosystem and quantify their dietary overlap. We used DNA metabarcoding on faecal samples to extract plant, fungal, and invertebrate DNA, identifying diet items and quantifying dietary range and overlap. The species' diets were similar, with a Pianka's overlap index score of 0.84 indicating high dietary similarity. Bush rats had a large dietary range, consisting of many plant and fungal species and some invertebrates, with almost no within‐species variation. Possums had a more restricted dietary range, consisting primarily of plants. We suggest that the larger dietary range of the bush rat helps buffer it from the impacts of competition from possums by providing access to more food types. We conclude that, despite the high ostensible overlap in the foods consumed by dietary generalist species, fine‐scale partitioning of food resources may be a key mechanism to alleviate competition and permit co‐existence.